2007
DOI: 10.1007/s00213-007-0757-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neural response to happy and sad faces by acute tryptophan depletion

Abstract: In both cortical and sub-cortical regions, the neural response associated with processing emotional faces is significantly modulated by 5HT manipulation resulting from ATD. Moreover, in certain areas, this effect of 5HT depends on the emotional valence of the stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 90 publications
(109 reference statements)
0
35
0
1
Order By: Relevance
“…Although a handful of studies have indicated that TRP-does alter brain activity and performance in PH-/FH-individuals during facial expression processing [60,62] , results are inconsistent. Additionally, behavioral and neuroimaging differences have been noted with TRP-on emotive facial processing between PH-and PH+ individuals [85] , consistent with indirect evidence suggesting that TRP-may alter brain activity differently in PH+/FH+ and PH-/FHgroups [86][87][88][89] .…”
Section: Limitations and Future Directionsmentioning
confidence: 84%
See 1 more Smart Citation
“…Although a handful of studies have indicated that TRP-does alter brain activity and performance in PH-/FH-individuals during facial expression processing [60,62] , results are inconsistent. Additionally, behavioral and neuroimaging differences have been noted with TRP-on emotive facial processing between PH-and PH+ individuals [85] , consistent with indirect evidence suggesting that TRP-may alter brain activity differently in PH+/FH+ and PH-/FHgroups [86][87][88][89] .…”
Section: Limitations and Future Directionsmentioning
confidence: 84%
“…One study found that TRP-increased negative facial expression processing in FH+ females [59] , while another found that it decreased fear but increased disgust recognition in remitted depressives [60] . Several studies in PH-/FH-individuals did not find altered performance on facial recognition tasks with TRP- [61,62] , although one found that it impaired fear recognition in healthy females [46] . Previous work in our laboratory indicated that TRP-enhanced early visual ERPs (P100, P200) to sad versus happy faces in FH+ individuals [16] .…”
Section: Serotonin and Facial Processingmentioning
confidence: 99%
“…Studies applying ATD in healthy subjects during fMRI revealed increased activity in frontal brain regions in response to emotional faces (Fusar-Poli et al 2007;Daly et al 2010) as well as during a Stroop task (Horacek et al 2005), whereas two studies using Go/Nogo paradigms showed decreased activity in frontal regions (Rubia et al 2005;Evers et al 2006). Cingulate activity was increased in one study (Fusar-Poli et al 2007) using emotional faces, but decreased in the other (Daly et al 2010), whereas insular activity was modulated in the opposite direction during emotional faces (decrease in Fusar-Poli et al 2007, increase in Daly et al 2010). Occipital cortical activity was decreased in both studies using emotional faces (Fusar-Poli et al 2007;Daly et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The insula cortex, which forms part of a so-called 'paralimbic' circuit is known to be important for the representation and monitoring of emotional states (Critchley et al, 2004), the superior temporal gyrus has been associated with the processing of both facial and other social stimuli (Habel et al, 2005;Ashwin et al, 2007;Barraclough et al, 2005) and the inferior frontal gyrus is important in impulsive behavior, which may be impaired in patients with depression. Indeed functionality within these regions is sensitive to serotonergic manipulations with SSRI administration (Smith et al, 2002;Anderson et al, 2007;Arce et al, 2008;Nemoto et al, 2003), and tryptophan depletion (Fusar-poli et al, 2007;Rubia et al, 2005). Although it is known that sub-populations of 5-HT neurons are present in the midbrain, their differential anatomical connectivity is not known.…”
Section: Discussionmentioning
confidence: 99%